EVALUATING THE INTERNAL CSR USING IMPORTANCE AND PERFORMANCE ANALYSIS (IPA) AT PT. PELABUHAN INDONESIA IV (PERSERO) TERMINAL PETIKEMAS BITUNG - Arline, Nadya .; Tumbuan, W.J.F Alfa; Tumiwa, Johan R. (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: Internal Corporate Social Responsibility has been heavily discussed in the academic research since the last decade. Despite the development of Internal Corporate Social Responsibility, focus of Internal Corporate Social Responsibility activities on employees has remained largely neglected. The aims of this study is to evaluate and measuring the Internal Corporate Social Responsibility such as Health and Safety, Human Rights, Training and Education, Work Life Balance, and Workplace Diversity using importance and performance analysis. The sample size of this research is 70 employee who work in PT. Pelabuhan Indonesia IV (PERSERO) Terminal Petikemas Bitung. The results showed that Health and Safety, Human Rights, and Work Life Balance are placed in Quadrant II (keep up the good work), while Training and Education and Workplace Diversity are placed in Quadrant III (low importance and low performance). So, related with the findings there will be several recommendation to the management of PT. Pelabuhan Indonesia IV (PERSERO) Terminal Petikemas Bitung.Keywords: internal CSR, importance and performance analysis.